Selected Decisions, 20th Ed. 1995. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper analyses several IMF's selected decisions of the Executive Board and selected documents. The Executive Board has reviewed the procedures relating to the IMF's surveillance over members' exchange rate policies. Whenever the Managing Director considers that important economic or financial developments are likely to affect a member's exchange rate policies or the behavior of the exchange rate of its currency, he shall initiate informally and confidentially a discussion with the member. A staff report will be circulated to the Executive Directors under cover of a note from the Secretary specifying a tentative date for Executive Board discussion which will be at least 15 days later than the date upon which the report is circulated. The bicyclic consultation procedure shall be terminated and each member currently on the bicyclic procedure shall be immediately placed on the standard 12-month cycle; the first consultation with each such member that is completed after the adoption of this decision shall be conducted in accordance with the procedures that apply to consultations under the standard 12-month cycle, and the deadline for completion that applied under the bicyclic procedure shall continue to apply to such consultation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet